The Influence of Traumatic Injuries Early Diagnosis on the Development of Pulmonary Complications in Patients With Multisystem Chest Trauma - E. S. Vladimirova; E. A. Tarabrin; I. E. Popova; E. D. Menshikova; S. A. Badygov; E. V. Kislukhina; L. V. Popkova (Неотложная медицинская помощь)
Despite the existing progress in providing care to patients with severe multisystem chest injury using advanced diagnostic methods, a high mortality rate still reaches 20–30%.Aim of study. To assess the impact of early diagnosis and correction of chest injuries on the development of complications in patients with multisystem trauma.Material and methods. The results of diagnosis and treatment of 89 patients with severe multisystem closed chest injury were studied. According to the time of admission to the Institute, the patients were divided into two groups: Group I, who were admitted to the Institute within the first hours after the injury (51 patients), and Group II, who were transferred from other medical institutions on the 3rd–7th day (38). CT was performed as a standard method of diagnosis and monitoring the dynamics of the process. With the development of purulent-inflammatory pulmonary complications, the bacteriological test of bronchoalveolar lavage was performed. Treatment included complex intensive therapy, drainage of the pleural cavity and emergency surgical interventions, if necessary.Results. In Group I, lung contusion occurred in 43 (84%) patients, and after 7-10 days, the contusion foci partially regressed in 20 (46.5%) patients. In 8 (16%) patients with lung rupture, infiltrative changes in the lung were resolved on the 18th-30th day, while 4 (50%) of them had pneumonia outside the contusion zones. In Group II, patients were put on a ventilator and inflammatory changes in the lungs were revealed in 30 patients (79%). Lung rupture associated with the contusion was revealed in 2 (5.2%). When comparing the groups by the composition of the isolated microflora, it was found that in patients of group II, Acinetobacter spp was more often found (46.7% vs. 17.1% in group I patients, p=0.021) and Enterococcus spp. (30.0% and 8.6%, respectively, p=0.058), as well as Klebsiella pneumoniae (46.7% and 37.1%, p=0.6). At the same time, Staphylococcus aureus was not found in these patients, while it was detected in 14.3% of patients from Group I (p=0.09). Medical care in Group I was carried out according to the principles of the “golden hour”: within the first hour from the moment of admission to the patients with the presence of pneumothorax and hemothorax, the pleural cavity was drained. In Group II, this procedure was performed in other medical institutions and in 5 additional patients at the Institute.Conclusions. Early computed tomography diagnosis of multisystem trauma makes it possible to assess the severity of injuries to the chest organs and other areas of the body and determine the treatment tactics. A comprehensive approach to the management of patients, including early diagnosis of trauma, drainage of the pleural cavity, determination of management tactics, bacterial test of the lower respiratory tract discharge, helps reduce infectious complications by an average of 45.46%.